Plasma metabolomics in male primary and functional hypogonadism - Grande, Giuseppe; De Toni, Luca; Garolla, Andrea; Milardi, Domenico; Ferlin, Alberto (Frontiers in Endocrinology, 2023)
Metabolomics proposes to unveil the molecular machinery involved in each specific disease by the comprehensive analysis of low-molecular-weight metabolites in a biological sample. This narrative mini-review analyzes previous studies applying ultra-high-performance liquid chromatography–high-resolution mass spectrometry (HRMS)-based metabolomics to highlight different metabolic pathways involved in male hypogonadism and testosterone replacement therapy, both in the case of insulin-sensitive patients with primary hypogonadism and in the case of insulin-resistant patients with functional hypogonadism. In functional hypogonadism, metabolomics revealed that different biochemical pathways are affected. In detail, glycolysis is the most important biochemical process involved in these patients. Glucose metabolism is fueled by amino acid degradation, and gluconeogenesis is widely stimulated. Some important pathways, including glycerol, are compromised. Furthermore, mitochondrial electron transport is influenced, namely, by a decrease in ATP production. On the contrary, beta-oxidation of short- and medium-chain fatty acids does not represent an energy source in hypogonadal patients. Both lactate and acetyl-CoA are converted into ketone bodies, which increased immensely. However, carnosine and β-alanine are greatly reduced. These metabolic changes are associated with increased fatigue and mental confusion. After testosterone replacement therapy, a complete restoration is achieved for only a part of the metabolites. It is of note that only in patients with functional hypogonadism treated with testosterone are ketone bodies produced at high levels, so the symptoms sometimes reported by these patients after the beginning of the therapy (difficulty in concentrating, depressed mood, brain fog, and memory impairment) might represent a specific “keto flu-like” syndrome, related to the metabolic ketonic state.